1997
DOI: 10.1152/jn.1997.78.3.1305
|View full text |Cite
|
Sign up to set email alerts
|

Different Roles of Neurons B63 and B34 That Are Active During the Protraction Phase of Buccal Motor Programs inAplysia californica

Abstract: The buccal ganglion of Aplysia contains a central pattern generator (CPG) that organizes sequences of radula protraction and retraction during food ingestion and egestion. Neurons B63 and B34 have access to, or are elements of, the CPG. Both neurons are depolarized along with B31/B32 during the protraction phase of buccal motor programs. Both cells excite the contralateral B31/B32 neurons and inhibit B64 and other neurons active during the retraction phase. B63 and B34 also both have an axon exiting the buccal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
210
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(217 citation statements)
references
References 45 publications
6
210
0
1
Order By: Relevance
“…FCAP-containing neurons and processes could be observed in the buccal and cerebral ganglia and the gut. Furthermore, both MALDI and IMM detected FCAPs in the CBC, a nerve that contains axons of CBIs and BCIs, two classes of neurons that are implicated in initiation and modulation of feeding motor programs (Rosen et al, 1991;Teyke et al, 1993;Hurwitz et al, 1997Hurwitz et al, , 1999Xin et al, 1999;Sanchez and Kirk, 2000;Jing and Weiss, 2001). We showed that FCAPs are present in several CBIs and BCIs, although the identity of these CBIs and BCIs remains to be defined.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…FCAP-containing neurons and processes could be observed in the buccal and cerebral ganglia and the gut. Furthermore, both MALDI and IMM detected FCAPs in the CBC, a nerve that contains axons of CBIs and BCIs, two classes of neurons that are implicated in initiation and modulation of feeding motor programs (Rosen et al, 1991;Teyke et al, 1993;Hurwitz et al, 1997Hurwitz et al, , 1999Xin et al, 1999;Sanchez and Kirk, 2000;Jing and Weiss, 2001). We showed that FCAPs are present in several CBIs and BCIs, although the identity of these CBIs and BCIs remains to be defined.…”
Section: Discussionmentioning
confidence: 60%
“…These neurons include the cerebral-buccal interneurons (CBIs) and buccal-cerebral interneurons (BCIs), which are known to be involved in generating and shaping the cerebral and buccal ganglion-mediated components of feeding motor programs (Rosen et al, 1991;Teyke et al, 1993;Hurwitz et al, 1997;Perrins and Weiss, 1998;Xin et al, 1999). Modulators that can alter feeding motor program output have been localized to some of the known CBIs and BCIs, and evidence suggests that additional, as yet unidentified neuropeptides are present in the feeding circuitry (Lloyd, 1989;Li et al, 1998).…”
mentioning
confidence: 99%
“…A Grass model S88 stimulator was used for stimulation. In addition to CBI-11 (Wu et al, 2003), all other neurons were identified as described previously (Rosen et al, 1991;Hurwitz et al, 1994;Hurwitz and Susswein, 1996;Weiss, 2001, 2002;Sasaki et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of the type of motor program, the phasing of the protractionretraction sequence remains constant. Protraction was monitored by recording from the I2 nerve, which contains the axons of protractor motor neurons B31/32 and B61/62 (Hurwitz et al, 1994). In some experiments, retraction was monitored by recording from retraction interneuron B64 (Hurwitz and Susswein, 1996).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation